Frequency of a romantic partner in a dream series - Schredl, Michael; Reinhard, Iris (Dreaming, 2012)
The continuity hypothesis of dreaming states that dreams reflect waking life experiences. As the romantic partner plays an important role in the waking life of the dreamer, it seems plausible that s/he is also often present in his or her dreams. In accordance with previous findings, the romantic partner was found in about 20% of the dreams during relationship periods in a long dream series lasting 11 years. In order to study factors that might affect the continuity between waking and dreaming, it would be interesting to correlate the frequency of partner dreams with day-time measures like intimacy or quarrelling. In addition, investigating the slope of the decline of partner dreams after separation also provided clues about factors affecting continuity between waking and dreaming.
Gesehen am 03.04.2018